Anchoring ESG in Local Waters: Meaning-Making of Sustainable Investment Among Makassar’s Elite - Amin, Andi Mustika (Malaqbi Publisher, 2025)
This study employs critical discourse analysis to investigate how High Net Worth Individuals (HNWIs) in Makassar, Indonesia, construct meaning around sustainable investment and ESG principles. Through elite interviews with 15–20 participants, findings reveal that global ESG frameworks undergo active localization, filtered through maritime cultural identity, hyper-local environmental priorities (e.g., coastal erosion, fisheries), and indigenous values like gotong royong (cooperation) and Siri’ (honor). Participants navigate tensions between profit imperatives and ethical stewardship by emphasizing pragmatic risk mitigation, intergenerational responsibility, and regionally visible impact. The research highlights how HNWIs strategically distance themselves from Western-centric ESG norms, positioning themselves as cultural mediators who reconcile global standards with Eastern Indonesia’s socio-ecological realities. These insights advocate for culturally literate sustainable finance strategies in emerging markets.